Development of Resilience Measurement Tools in the Indonesian Cultural Context - Reformasianto, Viki Love (Universitas Negeri Surabaya, 2024)
Background: Resilience is defined as a personal quality that allows a person to thrive in the face of adversity and the ability to survive in overcoming stress. In Indonesia, research on resilience instruments has been conducted, but it is still limited to population samples and is still specific to academic resilience. Objective: This study aims to modify the resilience measurement tool with the cultural context in Indonesia, namely The Connor-Davidson Resilience Scale (CD-RISC) with its five dimensions of personal competence, spirituality, self-acceptance, self-control, and self-confidence. Method: This study uses quantitative methods, data analysis used is factorial analysis with Confirmatory Factor Analysis (CFA), Multiple Indicators Multiple Causes (MIMIC). Results: The Connor-Davidson Resilience Scale (CD-RISC) is a model fit resilience measurement tool according to the Indonesian context which consists of 23 items with participants of student groups with undergraduate & postgraduate education levels. Conclusion: This study successfully modified and simplified the resilience measurement tool, The Connor-Davidson Resilience Scale (CD-RISC) into a fit model of resilience measurement tools according to the Indonesian context.